Checklist of the ancyrocephalids (Monogenea) parasitizing Tilapia species in Cameroon, with the description of three new species - Pariselle, Antoine; Bitja Nyom, Arnold R.; Bilong, Charles F. (Zootaxa, 2013)
A checklist of the 23 species of Ancyrocephalidae (Monogenea) parasitizing Tilapia species sampled from both sides of the Cameroon Volcanic Line is provided. As already reported elsewhere, Cichlidogyrus aegypticus in Cameroon shows two different shape of its vagina, and C. tilapiae, C. arthracanthus and C. tiberianus were found on a wide range of host species. Among the 23 studied species of Monogenea, three are considered new species and are described herein: Cichlidogyrus berminensis n. sp. from Tilapia bemini, characterized by a short penis with marked narrow heel, a simple and straight accessory piece ending in a large hook, and a medium sized pair of uncinuli I; Cichlidogyrus gillesi n. sp. from Tilapia guineensis, characterized by a large and trapezoid heel of the penis and a S-shaped and wrinkle walled vagina; and Scutogyrus vanhovei n. sp. from Tilapia mariae, characterized by the presence of a distinct swollen portion of the penis. From a parasite’s point of view, the CVL has no influence on species dispersion/distribution.